Directions of development and trends in the Polish anthropology during the post-war period - Drozdowski, Zbigniew; Dzierżykray-Rogalski, Tadeusz (Anthropological Review, 1982)
The authors begin their review article with brief statement concerning a pre-war state of Polish anthropology. Main part of the paper is devoted to restructuring of the discipline after 1950. Ort this background the authors describe present status of anthropology in Poland enumerating directions of rescarch, describing organizational structure of institutions in relation to rescarch and education.